Relationship of low doses of alcohol voluntarily consumed during adolescence and early adulthood with subsequent behavioral flexibility. Issue 7 (October 2017) - Fisher, Hayley; Bright, Nicholas; Gallo, Mark; Pajser, Alisa; Pickens, Charles L.
Abstract : Previous alcohol use is associated with impaired decision-making and impulsivity in humans, but the relationship between alcohol use and decision-making/impulsivity is unclear. In two experiments, we determined whether chronic intermittent access to alcohol during adolescence and early adulthood would alter or be correlated with performance in a go/no-go reversal task, a devaluation task, or operant extinction. Rats received 6 weeks of chronic intermittent access to 20% alcohol or water from postnatal day 26 to 66 and then behavioral testing was initiated 1.5–2.5 weeks later. We found no evidence that voluntary alcohol consumption altered behavior in either task. However, we found that rats that consumed more alcohol made fewer commission errors in reversal learning compared with rats that drank less. There was no relationship between alcohol consumption and reversal learning omission errors. Alcohol consumption was not correlated with the magnitude of the devaluation effect, but rats that consumed more alcohol showed faster extinction during the devaluation test. Our results suggest that the relationships between behavioral flexibility and alcohol consumption may represent individual differences. Future work will determine the neurobiological and genetic bases of these behavioral differences.